Study of the Quality of Medical Therapy and Adherence in Patients with Chronic Heart Failure (According to the COMPLIANCE Study) - E. T. Guseynova; N. P. Kutishenko; Yu. V. Lukina; S. N. Tolpygina; V. P. Voronina; S. V. Blagodatskih; O. M. Drapkina; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
Aim. Assess the medical therapy quality in patients with chronic heart failure (CHF) and patients' adherence to the treatment depending on the previous observation in a specialized medical center as part of an of an outpatient registry.Materials and methods. An analysis of the medical therapy quality in patients with CHF was carried out as part of the COMPLIANCE prospective observational study (NCT04262583). 72 patients with CHF verified according to the protocol were included in the study. The average age of the patients was 69.1±9.5 years (31% of women and 69% of men). Patients were divided into groups: those who first applied to a specialized department during the period of the study inclusion, or those who were previously observed in a specialized department. The general adherence assessment to medical therapy was carried out using the original questionnaire «The adherence scale of the National Society for Evidence-Based Pharmacotherapy» which was supplemented with questions to assess the actual adherence to specific medical drugs recommended for patients with CHF.Results. According to the results of the study, beta-blockers were prescribed to 70 (97.2%) patients. Angiotensin converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARBs) were recommended in 68 (94%) patients. Mineralocorticoid receptor antagonists were included in therapy in 6 out of 9 patients who were shown to be prescribed (66.6%). The choice of medical drugs within the group was not always adequate. For example, ACEi/ARBs with proven efficacy in patients with CHF were prescribed only in 72% of patients. Comparative analysis of adherence to medical therapy between patients of the selected groups demonstrated a higher adherence to the recommended therapy in patients who were previously observed in a specialized center.Conclusion. The medical therapy quality for patients with CHF doesn't always comply with current clinical guidelines. The choice of a medical drug within a group is not always adequate. Regular observation in a specialized center contributes to a higher adherence to the recommended therapy.